BERAKAR DAN BERTUMBUH DALAM KOLOSE 3:6-7 MENGHADAPI TANTANGAN DI MASA RESESI - Enny Irawati (STT BIBLIKA JAKARTA, 2022)
This study is intended to analyze the rooted and growing texts in Colossians 3:6-7 facing the challenges of the recession. This study uses a qualitative research method of taxonomic analysis by using inductive biblical interpretation research. based on two sub-focuses (1) Having received Christ Jesus (2) The power of believers. The results of the study show the importance of believers being rooted and growing in Christ, not sinning in making decisions in the midst of times, being able to be grateful for any blessings received. It can even remain a blessing to others when in the midst of adversity due to the impact of the recession. Keywords: Believers, rooted, growing, recession